Early hearing detection and intervention (EHDI) programmes for infants and young children in low-income and middle-income countries in Asia: a systematic review - Hannah Kuper; Deepashree Joshi B; Vidya Ramkumar; Lekha S Nair (BMJ Publishing Group, 2023)
Background Early hearing detection and intervention (EHDI) measures initiated in high-income countries (HICs) were attempted in low-income and middle-income countries (L&MICs). However, information regarding the models of EHDI, context-specific adaptations made to strategies and outcomes are not known.Aims The aims of this systematic review were to identify the various models of EHDI used in Asian L&MICs in the published scientific literature and to describe their efficacy and validity.Methods The studies were eligible if the programme was from Asian L&MICs, implemented for children below 6 years of age and published between 2010 and 2021. Google Scholar, PubMed, Web of Science, Scopus, EBSCOHost and EBSCO-CINAHL were used to find articles. Data were extracted from each selected article, and the risk of bias was assessed. The search results were summarised using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram. For primary outcomes, narrative synthesis was used, and forest plots were generated for secondary outcomes.Results In all, 82 studies were included, and these studies were divided into two categories: newborn and infant screening programmes and screening programmes for older children. Predominantly, a two-stage objective otoacoustic emission (Distortion Product/Transient Evoked) or automated auditory brainstem response screening, followed by a detailed auditory brainstem response to confirm the hearing loss, was used in newborn and infant screening programmes. Audiologists were the most frequent screening personnel. Screening of older children was mostly done by otolaryngologists, school instructors and nurses. They performed a single-stage pure tone audiometry screening followed by a detailed examination.Conclusion The screening tools and protocols used were similar to those used in HICs. However, no uniform protocols were followed within each country. Long-term viability of EHDI programmes was not known as there was limited information on impact outcomes such as cost-benefit.PROSPERO registration number CRD42021240341.